A Computational Approach to the Effects of Solvent on the Structural, Electronic, Spectroscopic (195Pt NMR and IR), and Thermochemical Properties of a Third‐Generation Anticancer Drug: Trans‐Platinum(II) Complex of 3‐Aminoflavone. Issue 8 (26th May 2017) - Ghiasi, Reza; Sadeghi, Nasrin
Abstract : This study evaluated the structural, electronic and thermochemical properties of an anticancer active molecule, i.e. trans ‐bis‐(3‐aminoflavone)dichloridoplatinum(II) ( trans ‐Pt(3‐af)2 Cl2 ; TCAP) in the gas and solution phases. The polarizable continuum model (PCM) model was used to perform the required calculations in five solvents with different polarities. Moreover, the dependencies of energetic aspects, structural, thermodynamic parameters and frontier orbital energies of the complex were also examined. Dependencies of the frequency shifts of u(CO), u(NH) and 195 Pt Chemical shifts on the solvent dielectric were investigated by Kirkwood–Bauer–Magat equation (KBM). The energies of platinum d‐orbitals and formal electron configurations of Pt atom were calculated by natural bond analysis (NBO). Abstract : The structural, electronic, and thermochemical properties of an anticancer active molecule trans ‐bis‐(3‐aminoflavone)dichloridoplatinum(II) ( trans ‐Pt(3‐af)2 Cl2 ; TCAP) in the gas and solution phases are reported. Dependence of ν (C–O), ν (N–H), and δ( 195 Pt) on the solvent dielectric was investigated by the Kirkwood–Bauer–Magat equation. The energies of platinum d orbitals and formal electronic configurations of the Pt atom were calculated by natural bond orbital (NBO) analysis.